Analysing the interplay of regional economic structures and COVID-19's impact on Irish regions - Luke McGrath (Regional Studies, Regional Science)
This paper analyses the regional economic impacts of COVID-19 in Ireland. The results show regional labour market impacts were related to pre-existing economic structures rather than infection rates. Drivers of the employment shock were found to be regional specialisms in tourism focused sectors. Cushions were provided by regional specialisms in agriculture, healthcare and the knowledge intensive service sectors. For more rural regions that appeared more resilient to the labour market shock, cushions were likely provided by employment in slower growth potential sectors. During the recovery phase, these cushions can become anchors contributing to regional divergence. Consequently, some regions less severely impacted by the pandemic shock may, in fact, face more difficult structural challenges in the longer term. The pandemic has thus exacerbated pre-existing structural issues that are likely related to the observed regional economic divergence and findings of regional development traps since the recovery from the previous recessionary period of the 2010s. The broad implication is that that the regional recovery from the pandemic will not be based purely on short term COVID-19 exposure. In general terms, regional policy should look beyond the initial pandemic shocks to the key underlying development issues. A central point here is that there are no quick transformational fixes rather long-term structural imbalances need to be met. The key policy challenge, in the Irish case, is to avoid the trend from the previous economic crisis of regional divergence during the recovery phase.